(untitled) (UNIZIK Journal of Marketing, 2024)
The study examined interpersonal relation skills in promoting entrepreneurship and private sector performance in Ekiti State. A descriptive survey research design was adopted for the study. The population of the study consisted the entire small and medium scale enterprise owners in Ekiti State. The sample size was 424 which were selected using Yamane sampling model. Primary data used for the study were gathered through a structured questionnaire. Data gathered were analyzed using multiple regression model. The study found that interpersonal relation skills (collaboration, inspiration and behavioural regulation) positively affect entrepreneurship and private sector performance